URGENSI ILMU BIMBINGAN DAN KONSELING PADA AKTIFITAS PENDIDIKAN DI SEKOLAH - Noorma Wanti (INSTITUT AGAMA ISLAM NEGERI METRO, 2022)
What is meant by “guidance and counseling science” is a branch of science that investigates comprehensive procedures or steps that support individuals (clients) in their efforts to grow as individuals, solve problems, and achieve various other goals. The relationship between the study of direction and guidance and human qualities produces many results in human existence, both directly and indirectly. Direction and guidance are closely related to the assistance of human government as a fundamental goal of individual life, which cannot be separated from the characteristics that prevail and grow in social society. Aspects of individual values set forth in a professional or scientific code of ethics must always be considered in providing guidance and counseling as well as in broadening one's knowledge.